A case of long-term 24-month survival in pancreatic anaplastic carcinoma (giant cell type) after S1 postoperative adjuvant chemotherapy. (2016) - Nitta, Toshikatsu; Fujii, Kensuke; Kataoka, Jun; Tominaga, Tomo; Kawasaki, Hiroshi; Ishibashi, Takashi
Highlights: The prognosis for patients with anaplastic carcinoma of the pancreas is reported much poorer even if resected. S-1 is more effective for anaplastic carcinoma of the pancreas. Adjuvant chemotherapy with S-1 in patients with resected anaplastic carcinoma of the pancreas is recommended. Abstract: We herein describe the case of a 70-year-old female patient diagnosed with pancreatic carcinoma. An abdominal enhanced computed tomography scan revealed a poorly enhanced mass (17 mm × 15 mm in size) in the pancreatic head. Magnetic resonance cholangiopancreatography revealed stenosis of the main pancreatic and common bile ducts caused by a mass-neighboring cyst. Based on these findings, we performed subtotal stomach-preserving pancreaticoduodenectomy. The patient demonstrated a good postoperative course, and was discharged from our hospital in remission 49 days after the surgery. Pathological findings confirmed that it was anaplastic pancreas carcinoma (giant cell type). After the surgery, we performed S-1 adjuvant chemotherapy 100 mg/day for four weeks, repeated similarly every six weeks for a total of four courses. We have followed this case for over 2 years so far with adjuvant chemotherapy, and no recurrence or metastasis has been revealed. Adjuvant chemotherapy with S-1 in patients with resected anaplastic carcinoma of the pancreas is also recommended as a result of Japan Adjuvant Study Group of Pancreatic Cancer 01(JASPAC-01) like the ordinary pancreatic ductal carcinomas. There is a possibility to achieve long-term survival in cases in which multidisciplinary treatment such as a curative resection and adjuvant chemotherapy are performed.